2021
DOI: 10.3389/fimmu.2021.634119
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling Identifies Neutrophil-Specific Upregulation of Cystatin F as a Marker of Acute Inflammation in Humans

Abstract: Cystatin F encoded by CST7 is a cysteine peptidase inhibitor known to be expressed in natural killer (NK) and CD8+ T cells during steady-state conditions. However, little is known about its expression during inflammatory disease states in humans. We have developed an analytic approach capable of not only identifying previously poorly characterized disease-associated genes but also defining regulatory mechanisms controlling their expression. By exploring multiple cohorts of public transcriptome data comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…For instance, CST7, CLEC5a, and NEDD4 indirectly interact with NLRC4 and RGL4 in gene networks and are also involved in immune regulation and inflammatory responses. Transcriptomic profiling has verified that neutrophil-specific upregulation of cystatin F (encoded by CST7) is a sign of acute inflammation in humans (46). CST7 is significantly upregulated in patients with sepsis compared to their expression in healthy controls (46)(47)(48).…”
Section: Discussionmentioning
confidence: 95%
“…For instance, CST7, CLEC5a, and NEDD4 indirectly interact with NLRC4 and RGL4 in gene networks and are also involved in immune regulation and inflammatory responses. Transcriptomic profiling has verified that neutrophil-specific upregulation of cystatin F (encoded by CST7) is a sign of acute inflammation in humans (46). CST7 is significantly upregulated in patients with sepsis compared to their expression in healthy controls (46)(47)(48).…”
Section: Discussionmentioning
confidence: 95%
“…Among the four populations, only 75 DEGs were identified. Among DEGs, only granule-related genes and genes highly expressed in neutrophils, including LPO, MPO, LYZ [ 41 ], ELANE, PRTN3, CSTG [ 42 ], CST7 [ 43 ], and CSTA were upregulated by differentiation into neutrophils ( Fig. 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A). We found that both in vivo- and in vitro- derived neutrophil-biased progenitors highly expressed neutrophil uni-expressed genes or granule-related genes, including MPO, LRG1 [ 45 ], PRTN3, ELANE, CTSG [ 42 ], CST7 [ 43 ], CSTA [ 46 ], and CLEC11A [ 47 ] ( Fig. 4 .…”
Section: Resultsmentioning
confidence: 99%
“…To that point, the growing repertoire of publicly accessible transcriptomic datasets, like those on the Gene Expression Omnibus (GEO), serves as a valuable resource for discovering novel predictors, diagnostic markers and disease progression markers. Diverse reductionist approaches have been used to successfully identify putatively novel genes/functions 5–9 and perform system‐level re‐analyses 10–12 …”
Section: Introductionmentioning
confidence: 99%